Effects of solid loading and calcination temperature on microstructure and properties of porous Si3N4 ceramics by aqueous gelcasting using DMAA system. Issue 16 (November 2019) - Yin, Shuang; Jiang, Senchuan; Pan, Limei; Guo, Lin; Zhang, Zhenghao; Zhang, Jingxian; Li, Xiaoyun; Qiu, Tai; Yang, Jian
Abstract: Herein, a low–toxic N, N–dimethylacrylamide (DMAA) system was used in preparation of porous Si3 N4 ceramics by aqueous gelcasting, and variations in microstructure and properties with solid loading and calcination temperature were systematically investigated. In the considered solid loading range of 28–44 vol%, all the slurries exhibited superior rheological properties (≤145 mPa⋅s at 95.40 s −1 for 44 vol% solid loading) perfectly suitable for casting. With increasing solid loading, a decreased bulk density (1.71–1.69 g/cm 3 ), volume shrinkage (37.73–13.77%) and flexural strength (46.56–26.75 MPa) of green bodies were obtained, exhibiting better mechanical properties than those derived from the conventional acrylamide (AM) system. Regarding Si3 N4 ceramics with various solid loadings, the increase in calcination temperature favored the phase transformation α→β–Si3 N4 and β–Si3 N4 growth, however, the increased solid loading exhibited an inhibiting effect on those since mass transport in gas phase was blocked due to the disruption of pore connectivity. The resulting microstructure changes imparted Si3 N4 ceramics increasing flexural strength (110.36–367.88 MPa), fracture toughness (2.54–5.03 MPa⋅m 1/2 ), as well as decreasing porosity (54.21–41.05%) and pore size (0.38–0.33 μm). This work demonstrates the potential research value of DMAA system in preparing high–performance porous Si3 N4 ceramics through gelcasting technique.